An Overview of Agricultural Pollution in Vietnam : The Crops Sector - Nguyen, Tin Hong (World Bank, Washington, DC, 2018)
The “study” constitutes the totality of the work and includes multiple components,including national overviews of agricultural pollution for the three focus countries, thematic working papers, and an overall synthesis report. The present report corresponds to the national overview of agricultural pollution in Vietnam, and specifically, to the background paper on crop-related pollution. It provides a broad national overview of (a) the magnitude, impacts, and drivers of pollution related to the crop sector’s development; (b) measures that have been taken by the publicsector to manage or mitigate this pollution; and (c) existing knowledge gaps and directions for future research.The report was prepared on the basis of a desk review of existing literature, recentanalyses, and national and international statistics. It did not involve new primaryresearch and did not attempt to cover pollution issues that arise in crop value chainsmore broadly, outside the farm gate—such as from processing, transportation, andthe manufacturing of agricultural inputs and machinery. An earlier version of the report was circulated to stakeholders representing national government agencies,nongovernmental organizations (NGOs), and research institutions, and discussed at a stakeholder consultation workshop in December 2016.This paper is structured into seven main sections. Section one includes the background and analytical framework; Section two reviews the intensification and expansion of the agricultural sector through various development stages, with a special focus on selected crops of rice, maize, and coffee; Section three discusses the use of inputs in crop systems as well as waste management practices, with a special focus on the use of fertilizers and pesticides in the selected crops; Sections four and five review thephysical and socioeconomic impacts (that is, water, soil, and air pollution and impacts on ecosystems and public health); Section six discusses the driving factors contributing and responding to agricultural pollution; Section seven presents the solutions and knowledgegaps; and Section eight summarizes the findings and recommendations.